Analysis of an MOS inverter with non‐uniform impurity profile - Agrawal R.; Dwivedi R.; Srivastava S.K. (My University, 2025)
An analytical model, for drain current and voltage characteristics of n‐channel enhancement mode MOSFETs, developed in a previous work using a displaced Gaussian profile, is now applied to analyse an inveter. It is observed that MOSFETs having non‐uniform impurity profile below the gate region have higher conductivity in the non‐saturation region as compared with those having uniform doping, whereas the conductivity in the saturation region is reversed. It is found that an inverter with both transistors having non‐uniform doping profile switches from high to low state at lower input voltages as compared to the inverter with both transistors having uniform doping profiles. This will help in designing an MOS inverter without much geometrical constraints of the device. Copyright © 1989 WILEY‐VCH Verlag GmbH & Co. KGaA